BS EN 3525. Aerospace series. Steel 15CrMoV6 (1.7334). Air melted. Hardened and tempered. Plates. 6 mm ≤ a ≤ 20 mm. 1 080 MPa ≤ Rm ≤ 1 280 MPa. (18th March 2021) - British Standards Institution,
No abstract available